Analisis Persepsi Lulusan KPI IAI AL-AZIS terhadap Konten “Seluruh Umat Muslim Harus Kompak” dalam Tinjauan Jurnalisme Profetik (Studi pada Channel Youtube LognewsTV) - Rafif Ahmad Fadilah; Ahmad Asrof Fitri; Elang Bachrudin (AN-NASHIHA Journal of Broadcasting and Islamic Communication Studies, 2025)
This study was motivated by the increasing use of social media, particularly YouTube, as a means of digital preaching in the modern era. The LognewsTV channel, through its video ‘All Muslims Must Be United,’ presents a message about the importance of unity among Muslims, religious values, and social tolerance. This study aims to analyse the perceptions of graduates of Islamic Communication and Broadcasting (KPI) towards this content from the perspective of Prophetic Journalism. The approach used is descriptive qualitative with data collection techniques through interviews, observation, and documentation. The research informants consisted of eight KPI graduates from IAI AL-AZIS from the 2013–2020 batches, who were selected purposively. The results showed that the video was considered successful in conveying the main messages about ukhuwah Islamiyah (Islamic brotherhood), respect for differences, and the spirit of cross-group collaboration. In cognitive, affective, and conative aspects, the informants understood the value of unity, felt positive emotions, and were encouraged to spread the message of da'wah. However, technically, the long duration and monotonous visuals were noted as areas for improvement. From a Prophetic Journalism perspective, this content reflected the values of Shiddiq, Amanah, Tabligh, and Fathonah, although the emotional delivery needed to be balanced with more informative and contextual presentation. In general, YouTube was considered effective as a medium for da'wah, but the presentation strategy needed to be improved to make it more relevant for the younger generation.